2010
DOI: 10.1103/physrevlett.104.167204
|View full text |Cite
|
Sign up to set email alerts
|

Valence-Band Structure of the Ferromagnetic Semiconductor GaMnAs Studied by Spin-Dependent Resonant Tunneling Spectroscopy

Abstract: The valence-band structure and the Fermi level (E(F)) position of ferromagnetic-semiconductor GaMnAs are quantitatively investigated by electrically detecting the resonant tunneling levels of a GaMnAs quantum well (QW) in double-barrier heterostructures. The resonant level from the heavy-hole first state is clearly observed in the metallic GaMnAs QW, indicating that holes have a high coherency and that E(F) exists in the band gap. Clear enhancement of tunnel magnetoresistance induced by resonant tunneling is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 22 publications
7
44
0
Order By: Relevance
“…Throughout the text we have provided arguments and references to relevant theory that supports an IB description for our data. Furthermore, the conclusion of the presence of a Mn-induced IB is supported by numerous previous studies of the electronic structure in FM Ga 1−x Mn x As 2, 10,22,28,29,35,56,[59][60][61] . Nonetheless, despite the experimental and theoretical support for an IB picture Ga 1−x Mn x As mentioned above, the experimental reality of the precise degree of separation between, and "mixing" of, impurity states and valence states remains unresolved.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Throughout the text we have provided arguments and references to relevant theory that supports an IB description for our data. Furthermore, the conclusion of the presence of a Mn-induced IB is supported by numerous previous studies of the electronic structure in FM Ga 1−x Mn x As 2, 10,22,28,29,35,56,[59][60][61] . Nonetheless, despite the experimental and theoretical support for an IB picture Ga 1−x Mn x As mentioned above, the experimental reality of the precise degree of separation between, and "mixing" of, impurity states and valence states remains unresolved.…”
Section: Discussionsupporting
confidence: 72%
“…Nonetheless, despite the experimental and theoretical support for an IB picture Ga 1−x Mn x As mentioned above, the experimental reality of the precise degree of separation between, and "mixing" of, impurity states and valence states remains unresolved. Analysis of resonant tunneling experiments has supported a strictly detached IB with remarkably little exchange splitting of the VB 29,61 . The interpretation of these tunneling data, however, has not been universally accepted (see Ref.…”
Section: Discussionmentioning
confidence: 95%
“…Our RIXS results show that the dominant charge transferred states are the trivalent Mn 3+ ground state and indicates the presence of a ligand hole bound to the Mn configuration. This arrangement will significantly reduce ionized impurity scattering and support the presence of quantum states in Ga 1−x Mn x As quantum wells observed by resonant tunneling spectroscopy [10,34].…”
supporting
confidence: 53%
“…We found that the following two ways are effective to increase T C and to enhance resonant tunneling to a certain degree. 51 One is to reduce the QW thickness for inducing stronger quantization, and the other is to use paramagnetic AlMnAs as an upper tunnel barrier of the GaMnAs QW. As described above, we found that T C of the lower GaMnAs layer can be increased to 60-70 K even when its thickness is thin (2 nm) by using a paramagnetic AlMnAs tunnel barrier in the GaMnAs single-barrier MTJ structures.…”
Section: Enhanced Resonant Tunneling and Tmr In Rtds With A Thin Gamnmentioning
confidence: 99%